2014
DOI: 10.1111/apa.12692
|View full text |Cite
|
Sign up to set email alerts
|

Safe oxygen saturation targeting and monitoring in preterm infants: can we avoid hypoxia and hyperoxia?

Abstract: Oxygen is a neonatal health hazard that should be avoided in clinical practice. In this review, an international team of neonatologists and nurses assessed oxygen saturation (SpO2) targeting in preterm infants and evaluated the potential weaknesses of randomised clinical trials.ConclusionSpO2 of 85–89% can increase mortality and 91–95% can cause hyperoxia and ill effects. Neither of these ranges can be recommended, and wider intermediate targets, such as 87–94% or 88–94%, may be safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 67 publications
2
102
1
13
Order By: Relevance
“…52 The mechanism(s) by which maintaining lower oxygen saturation levels might increase the risk of death is unclear, as the data from these trials suggest that tissue hypoxia was unlikely to be a factor. 23 In particular, in the SUPPORT trial, the proportion of infants with median oxygen saturations <85% was no different between the low and high saturation groups. 43 Conversely, a post hoc analysis from the SUPPORT trial found a disproportionally higher mortality rate in small-forgestational-age infants in the lower oxygen saturation target group, suggesting a possible interaction 54 ; if this observation can be confirmed in the other oxygen saturation trials, and more importantly in the individual patient analysis, it would suggest that small-for-gestational-age infants may be more vulnerable to lower oxygen saturations.…”
Section: Randomized Clinical Trials Of Oxygen Targetingmentioning
confidence: 88%
See 2 more Smart Citations
“…52 The mechanism(s) by which maintaining lower oxygen saturation levels might increase the risk of death is unclear, as the data from these trials suggest that tissue hypoxia was unlikely to be a factor. 23 In particular, in the SUPPORT trial, the proportion of infants with median oxygen saturations <85% was no different between the low and high saturation groups. 43 Conversely, a post hoc analysis from the SUPPORT trial found a disproportionally higher mortality rate in small-forgestational-age infants in the lower oxygen saturation target group, suggesting a possible interaction 54 ; if this observation can be confirmed in the other oxygen saturation trials, and more importantly in the individual patient analysis, it would suggest that small-for-gestational-age infants may be more vulnerable to lower oxygen saturations.…”
Section: Randomized Clinical Trials Of Oxygen Targetingmentioning
confidence: 88%
“…50 In the 1187 infants monitored with the revised algorithm, those assigned to the lower target range had a significantly increased mortality rate at 36 weeks' gestational age (23 46 a pooled analysis from all 3 BOOST-II sites, as originally planned, showed no significant difference in this outcome between the 2 arms (46.8% in the lower vs 43.4% in the higher saturation group; P = .10). 47 Two-year outcomes for the COT were published.…”
Section: Randomized Clinical Trials Of Oxygen Targetingmentioning
confidence: 92%
See 1 more Smart Citation
“…A great deal is known about the short-term and long-term consequences of hyperoxia, but not so much about the effects of hypoxia. Experiments have shown that fluctuations in oxygen saturation in arterial blood, even within values considered to be normal, may increase the incidence of ROP, but also reduce it (30).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Some experts have suggested reducing the lower limit of SpO 2 alarm to the high 80s. 32 Target ranges should not be equated to alarm settings. Alarm limits (lower limit of 89% and upper limit of 96%) have not been rigorously studied, but may offer a practical solution.…”
Section: Conclusion and Practical Recommendationsmentioning
confidence: 99%